2023
DOI: 10.7759/cureus.49647
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends and Factors Associated With Mortality Rate in Psychoactive Substance Use-Related Mental and Behavioral Disorders: A CDC-WONDER Database Analysis

Okelue E Okobi,
Ngozi T Akueme,
Amogechukwu O Ugwu
et al.

Abstract: BackgroundThe persisting challenge of substance use disorder's impact on society prompts the need for insights into its mortality trends. This study examines epidemiological patterns and factors tied to mortality rates in individuals with psychoactive substance-related mental and behavioral disorders from 1999 to 2020. MethodologyThis study used a retrospective observational design. The study analyzed the Centers for Disease Control and Prevention's (CDC) Wide-ranging Online Data for Epidemiologic Research (WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…This section explores some of the recent trends and challenges in epidemiological research, as highlighted in various studies. Okobi et al (2023) analyzed epidemiological trends and factors associated with mortality rates in psychoactive substance use-related mental and behavioural disorders. Their study, utilizing the CDC-WONDER database, revealed variations in mortality across genders, ages, and ethnicities, with males exhibiting higher mortality than females.…”
Section: Emerging Trends and Challenges In Epidemiological Researchmentioning
confidence: 99%
“…This section explores some of the recent trends and challenges in epidemiological research, as highlighted in various studies. Okobi et al (2023) analyzed epidemiological trends and factors associated with mortality rates in psychoactive substance use-related mental and behavioural disorders. Their study, utilizing the CDC-WONDER database, revealed variations in mortality across genders, ages, and ethnicities, with males exhibiting higher mortality than females.…”
Section: Emerging Trends and Challenges In Epidemiological Researchmentioning
confidence: 99%